Legal regulation of the central bank of Iraq: comparative study - زغير, امير حسن; عبد القادر, بان صلاح (Journal of Legal Sciences, 2021)
The emergence of the central bank was a commercial bank the advantage of the government as if it belonged to him or the privilege of issuing banknotes. There is no comprehensive definition contrary to the concept of the central bank although everyone agrees that the central bank stands at the head of the banking system in the state and takes charge of banking and credit policy in the country.The central bank is a governmental institution that dominates the monetary and banking system of the state it is responsible for issuing cash and acting as the financial agent of the government in addition to credit central in order to support the economic growth and monetary stability of the country and the central role of the central bank which in turn has become his main function. And the independence of the central bank in terms of monetary legal financial and administrative implications on the reality leads to achieve its objectives with high efficiency because it is far from the political influences and also provides him with credibility and transparency in the work through the dissemination and provision of financial and financial information to the public. Independence does not mean the complete separation between the central bank the government because it is an institution operating within the institutional framework of the state. Also independence does not mean the separation or the intersection of monetary policy from other policies especially the economic economy.The independence force comes from the coordination and integration of harmonious policies. The central bank represents the heart of the national monetary and financial economy and the importance of the legal system of the central bank lies in giving in the legal financial and administrative independence and determining its relation to the legislative authority and accurately defining its functions and determining its  functions and objectives by achieving full use economic growth stability of prices and the text on the independence of the central bank in terms of drawing his monetary policy away from the intervention of any party and the statement of how to from his administration in terms of appointment and honesty and dismissal as well as the statement of monetary and financial balance is a necessary condition to achieve its objectives ideally to perform its functions the law of the central bank of Iraq (56) of 2004 specifies all this and grants it financial administrative and legal independence the council of representatives is fully accountable for the performance of its functions and the drawing up and preparation of monetary policy in accordance with economic conditions and requirements independently of political circumstances.